HAMILTONIAN CYCLES IN WIJAYA KUSUMA FLOWER GRAPH - Nurdin, Susilawati; Nasution, Dinda Khairani (Departemen Matematika dan Sains Data FMIPA Universitas Andalas Padang, 2025)
In 1856, William Rowan Hamilton introduced the Icosian game. From this game, the concept of a Hamiltonian graph is defined. Hamiltonian graph is a graph that contains the Hamiltonian cycle, which is a cycle that passes through each vertex exactly once. We constructed a new class of graph which is inspired by the Wijaya Kusuma flower. In this article, we study the Hamiltonian properties of the Wijaya Kusuma flower graph. Based on the proof, it is concluded that the Wijaya Kusuma flower graph is a Hamiltonian graph.